The genus Alysson Panzer (Hymenoptera: Crabronidae) of China, with descriptions of two new species - Zou, Kun; Ma, Li; Chen, Guo-Hua; Li, Qiang (Zootaxa, 2025)
The genus Alysson Panzer, 1806 (Hymenoptera: Crabronidae: Bembicinae: Alyssontini) of China is reviewed. Two newly discovered species, Alysson cyanotaeniatus Zou and Chen sp. nov. and Alysson labrisectus Zou and Li sp. nov. are described and illustrated. A key to the Chinese species of Alysson is provided.